Differences of statin activity in 2D and 3D pancreatic cancer cell cultures - Paškevičiūtė M; Petrikaitė V (Dove Medical Press, 2017)
Miglė Paškevičiūtė,1 Vilma Petrikaitė1,21Department of Drug Chemistry, Faculty of Pharmacy, Lithuanian University of Health Sciences, Kaunas, Lithuania; 2Department of Biothermodynamics and Drug Design, Vilnius University Institute of Biotechnology, Vilnius, LithuaniaPurpose: To evaluate the anticancer activity of lovastatin (LOVA), mevastatin (MEVA), pitavastatin (PITA), and simvastatin (SIMVA) in 2D and 3D models of three human pancreatic cancer cell lines (BxPC-3, MIA PaCa-2, and PANC-1).Methods: The effect of statins on cell viability was estimated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide test. The activity of statins in 3D pancreatic cancer cell cultures was examined by measuring the size change of spheroids. The type of cell death was identified by cell staining with Hoechst 33342 and propidium iodide. The activity of statins on the clonogenicity of cancer cells was tested by evaluating the effect on the colony-forming ability of cells.Results: The rank order of the activity of tested statins on cell viability was as follows: PITA > SIMVA > LOVA > MEVA. Among the tested statins, PITA had the greatest effect on cell viability (half maximal effective concentration values after 72 h on BxPC-3, MIA PaCa-2, and PANC-1 cells were 1.4±0.4 µM, 1.0±0.2 µM, and 1.0±0.5 µM, respectively). PITA also showed the strongest effect on tumor spheroid growth. Statins suppressed the colony formation of cancer cells. PITA demonstrated the greatest reduction in colony size and number. Apoptosis and necrosis assay results showed that at lower concentrations statins mostly induced cell death through apoptosis, whereas higher concentrations of compounds activated also necrotic processes.Conclusion: Statins, especially PITA, demonstrate an anticancer activity against pancreatic cancer cell lines BxPC-3, MIA PaCa-2, and PANC-1 in both 2D and 3D models.Keywords: HMG-CoA reductase, cell viability, spheroid, apoptosis